A need-adapted transition program after pediatric kidney transplantation - Rieger Susanne; Bethe Dirk; Bagorda Angela; Treiber Dorothea; Beimler Jörg; Sommerer Claudia; Höcker Britta; Fichtner Alexander; Vinke Tobias; Zeier Martin; Hoffmann Georg Friedrich; Tönshoff Burkhard (De Gruyter, 2019)
A successful transition of renal transplant recipients from pediatric to adult care requires a structured, need-adapted and multidisciplinary approach to preserve renal graft function during this critical period of life. In this article we present our clinical protocol for transition from pediatric to adult care, which we developed on the basis of the International Society of Nephrology (ISN)/International Pediatric Nephrology Association (IPNA) consensus guidelines influenced by our own experience. This transition program was established in our center in July 2017. The entire transition process is structured and accompanied by a transition key worker (social worker). From 12 years of age we train pediatric renal transplant recipients in medical knowledge, self-management skills and networking with self-help groups. The training is adapted to the individual patient's intellectual ability, lasts about 10 years and takes place with increasing intensity. Repeatedly we perform standardized informational interviews and check patient's knowledge of transplant-related topics. Psychosocial and educational issues are evaluated concomitantly. The actual transfer takes place in a pediatric-adult-transition clinic. Relevant medical and psychosocial aspects are discussed and the future treatment regimen is established. The date of transfer is adapted to the individual patient's need; it varies between 18 and 24 years of age. In periods of increased risk for non-adherence the transfer is postponed to intensify the efforts for training and assistance. After transfer a standardized evaluation of each individual patient takes place focusing on medical and psychosocial issues and on satisfaction with the transition process. Collection of these data is still in progress and will be analyzed systematically at a later stage in order to evaluate the impact of this new transition program on the stability of transplant function. That analysis might serve as a basis for negotiations about refunding with health insurance companies.